Pectoral and trapezoidal flaps for reconstruction of full-thickness post-resection defect in combination treatment of locally advanced buccal cancer - D. V. Sikorsky; S. О. Podvyaznikov; A. N. Volodin; K. V. Bazanov; E. A. Molkova; M. I. Kopeykina; A. A. Egorov; M. A. Kurochkina (Опухоли головы и шеи, 2019)
The study objective is to compare short-term results of reconstruction of a full-thickness defect of the cheek using pectoral and trapezoidal flaps.Materials and methods. Examination and treatment of 21 patients with locally advanced buccal cancer were performed at the Nizhny Novgorod Regional Clinical Oncologic Dispensary in 2007–2018.Results. Flap necrosis developed in 7 (33 %) patients: in 3 patients total, in 4 – marginal. No postoperative mortality was observed. For pectoral flap reconstruction, necrosis was observed in 2 cases (marginal necrosis of the skin graft). For trapezoidal flap buccal reconstruction, necrosis was observed in 5 patients (total in 3, marginal in 2).Conclusion. Use of a trapezoidal flap is limited due to its anatomical characteristics and is associated with higher rate of necrosis despite better esthetic characteristics compared to a pectoral flap. Despite its larger volume compared to trapezoidal flap, pectoral flap has better blood supply which leads to low rate of necrosis.